A Singular Perturbation Based Global Dynamic High Gain Scaling Control Design for Systems With Nonlinear Input Uncertainties - Krishnamurthy, Prashanth; Khorrami, Farshad (IEEE transactions on automatic control, 2013)
A general class of uncertain nonlinear systems with input nonlinearities is considered. The system structure includes a core nominal system of triangular structure with additive uncertain nonlinear functions. The control input is allowed to enter non-affinely into the system dynamics as well as to have uncertainties coupled with it in terms of an uncertain nonlinear function of the input and output. The control design is based on dual controller/observer dynamic high-gain scaling with an additional dynamic scaling based on a singular-perturbation-like redesign to address the non-affine and uncertain nature of the input appearance into the system dynamics. The proposed approach yields a global robust adaptive output-feedback control design.